A Note on the Reproductive Consequence of Fruit Feeding in Mallotus philippensis (Lam.) M. Arg. - Rawat, Krishna Kumar; Gupta, Dayanidhi; Sahai, Kanak (Indian Forester, 2019)
Insect feeding of ripening fruits and seeds prior to dispersal creates massive losses in reproductive success in many plant species. Mallotus philippensis, an economically and medicinally important plant species is very prone to pathogen and infestation. The developing and mature fruits of Mallotus philippensis were attacked by a variety of herbivore insect that damage fruit and seed yield. The aim of the study is to determine the influence of insect feeding on the reproductive success of Mallotus philippensis by studying the injury pattern caused by insect feeding and its ultimate damage to the fruit and seeds. The study was conducted in three consecutive years from 2014 to 2016. Various insect feeders were collected and identified. Two feeding guilds were observed; one that preferably fed on the developing and mature fruits, i.e. Cantao ocellatus Thunberg, Physopelta gutta Burmeister and Physopelta schlanbuschii Fabricius; and others that were present on the young vegetative parts of the tree like shoot, petiole and foliage, i.e. mealy bugs, Aconophora and caterpillars of unidentified insect taxa. The most frequent insect feeder was identified as Physopelta schlanbuschii. Feeding is one of the major threats to the reproductive success of Mallotus philippensis growing in the tropical moist deciduous forest of India.